Oar-miR-432 Regulates Fat Differentiation and Promotes the Expression of BMP2 in Ovine Preadipocytes - Jin, Meilin; Fei, Xiaojuan; Li, Taotao; Lu, Zengkui; Chu, Mingxing; Di, Ran; He, Xiaoyun; Wang, Xiangyu; Wang, Yuqing; Yuan, Zehu; Quan, Kai; Wang, Huihua; et al. (Frontiers in Genetics, 2022)
The fat tail is a unique characteristic of sheep that represents energy reserves and is a complex adaptative mechanism of fat-tailed sheep to environmental stress. MicroRNA play a significant role as regulators at the post-transcriptional level, but no studies have explained the molecular mechanisms of miRNA which regulate fat deposition in sheep tails. In this study, mRNA and miRNA analysis examined tail fat tissue from three Hu fat-tailed and three Tibetan thin-tailed sheep. After aligning to the reference sequences, 2108 differentially expressed genes and 105 differential expression miRNAs were identified, including 1247 up- and 861 down-regulated genes and 43 up- and 62 down-regulated miRNAs. Among these differential expression miRNAs, oar-miR-432 was one of the most down-regulated miRNAs between Hu sheep and Tibetan sheep and 712 genes were predicted to be targeted by with oar-miR-432, 80 of which overlapped with DEGs. The Gene Ontology analysis on these genes showed that BMP2, LEP, GRK5, BMP7 and RORC were enriched in fat cell differentiation terms. The genes for BMP2 targeted by oar-miR-432 were examined using dual luciferase assay. The oar-miR-432 mimic transfected into preadipocytes resulted in the increased expression of BMP2. The marker gene PPAR-γ of fat differentiation had a lower expression than the negative control on days 0, 2 and 4 after induced differentiation. The number of lipids drops in the oar-miR-432 mimic group detected by oil red O stain was also less than the negative control. This is the first study to reveal the fat mechanisms by which oar-miR-432 inhibits fat differentiation and promotes the expression of BMP2 in sheep tails.